2015
DOI: 10.1007/s10661-015-4300-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the application of various wastewater sludges on the properties of sandy soil

Abstract: This research was conducted to determine the effect of various wastewater sludge (domestic type (B), mixture of industry and domestic type (L), aerobic food industry (P), anaerobic food industry (M)) levels on the properties of sandy soil, including pH, electrical conductivity (EC), and the levels of available N (NH4 and NO3) and P, diethylenetriamine pentaaceticacid (DTPA)-extractable microelements and heavy metals. An incubation experiment was performed in which sludges were applied at rates of 0, 40, 80, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…It was believed that soil NH 4 + -N converted to NO 3 − -N under the process of nitrification, when N was more available after SS input. Asik et al [74] also, in an incubation experiment, demonstrated change patterns where soil NH 4 + -N content decreased and NO 3 − -N content increased with sludge applied from 0 to 160 t ha −1 over a period of 150 days. In this study, we found that soil NO 3 − -N and NH 4 + -N were significantly positively correlated with soil water content (r = 0.738, p < 0.01; r = 0.640, p < 0.05, respectively) and significantly nega-tively correlated with soil bulk density (r = −0.709, p < 0.01; r = 0.656, p < 0.05, respectively) (Table 4).…”
Section: Responses Of Soil Properties To Ss Applicationmentioning
confidence: 88%
“…It was believed that soil NH 4 + -N converted to NO 3 − -N under the process of nitrification, when N was more available after SS input. Asik et al [74] also, in an incubation experiment, demonstrated change patterns where soil NH 4 + -N content decreased and NO 3 − -N content increased with sludge applied from 0 to 160 t ha −1 over a period of 150 days. In this study, we found that soil NO 3 − -N and NH 4 + -N were significantly positively correlated with soil water content (r = 0.738, p < 0.01; r = 0.640, p < 0.05, respectively) and significantly nega-tively correlated with soil bulk density (r = −0.709, p < 0.01; r = 0.656, p < 0.05, respectively) (Table 4).…”
Section: Responses Of Soil Properties To Ss Applicationmentioning
confidence: 88%
“…2018 magnésio e potássio (NASCIMENTO et al, 2004;UNAL;KATKAT, 2009); de fósforo, cálcio e capacidade de troca catiônica (CTC) (NASCIMENTO et al, 2004); da condutividade elétrica, do carbono orgânico total e da atividade microbiana (MINGORANCE et al, 2014); e do fósforo disponível e da condutividade elétrica (UNAL; KATKAT, 2009;ASIK et al, 2015). Apesar dos benefícios que a aplicação do lodo pode proporcionar, alguns componentes indesejáveis dos efluentes podem se concentrar no lodo, tais como metais pesados, poluentes orgânicos e microrganismos patogênicos (SILVA et al, 2001).…”
unclassified
“…Apesar dos benefícios que a aplicação do lodo pode proporcionar, alguns componentes indesejáveis dos efluentes podem se concentrar no lodo, tais como metais pesados, poluentes orgânicos e microrganismos patogênicos (SILVA et al, 2001). A aplicação do lodo pode causar acúmulo de metais no solo (SILVA et al, 2006;ASIK et al, 2015) e em plantas de milho (SILVA et al, 2006), além de apresentar risco de contaminação das águas subterrâneas com nitrato (DYNIA et al, 2006). Dessa forma o presente trabalho avaliou o desenvolvimento de plantas agrícolas e plantas nativas (aspectos químicos e físicos) com a aplicação de lodo do esgoto doméstico.…”
unclassified